The Effectiveness of Talent Management on Malaysian SME Performance : An Exploratory Study - Kamaruzzaman, Irwan Kelana (2014)
Talent has become the most critical success factor in creating strategic value for today‟s organizations. While traditional corporate assets such as physical and financial capital are essential to move economies, knowledge assets have become equally important (if not more) and the only sustainable form of capital is the intellectual capital. Firms can have same technologies and equally strong financial might, but it is the human capital, or talent, that ensures continuous learning for organizations to compete in today‟s knowledge based economy. The strategic importance of talent must be at the top priority of business leaders if they were to create talent powered organizations. To thrive, talent management needs to the embedded into the very fabric of the organization. Organizations, large or small, vary in their approach to talent management. As large companies are known to have formalized talent management system to attract and retain talents, same cannot be said for small and medium enterprises (SME). SMEs, made up of different characteristics have different talent management practices among them. Micro companies have an informal approach to talent management while small and medium companies have a rather structured approach to attract and retain talents. Interviews were carried out among 5 SME owners and 1 employee of an SME to explore the practices and the impact of their talent management practices. The results indicates there are four key take aways from the research - SMEs interviewed must offer compelling EVPs and engage with employees, SMEs have different talent management styles due to their different profiles and characteristics, the extent of talent management in SMEs depends on their level of competitiveness, and talent management will either positively or negatively impact SMEs performance.